A Targeted Gene Panel for Circulating Tumor DNA Sequencing in Neuroblastoma - Cimmino, Flora; Lasorsa, Vito Alessandro; Vetrella, Simona; Iolascon, Achille; Capasso, Mario (Frontiers in Oncology, 2020)
Background: Liquid biopsies do not reflect the complete mutation profile of the tumor but have the potential to identify actionable mutations when tumor biopsies are not available as well as variants with low allele frequency. Most retrospective studies conducted in small cohorts of pediatric cancers have illustrated that the technology yield substantial potential in neuroblastoma. Aim: The molecular landscape of neuroblastoma harbors potentially actionable genomic alterations. We aimed to study the utility of liquid biopsy to characterize the mutational landscape of primary neuroblastoma using a custom gene panel for ctDNA targeted sequencing. Methods: Targeted next-generation sequencing (NGS) was performed on ctDNA of 11 patients with primary neuroblastoma stage 4. To avoid the detection of false variants, we used UMIs (unique molecular identifiers) for the library construction, increased the sequencing depth and developed ad hoc bioinformatic analyses including the hard filtering of the variant calls. Results: We identified 9/11 (81,8%) patients who carry at least one pathogenic variation. The most frequently mutated genes were KMT2C (5 cases), NOTCH1/2 (4 cases), CREBBP (3 cases), ARID1A/B (3 cases), ALK (2 cases), FGFR1 (2 cases), FAT4 (2 cases) and CARD11 (2 cases). Conclusions: We developed a targeted NGS approach to identify tumor-specific alterations in ctDNA of neuroblastoma patients. Our results show the reliability of our approach to generate genomic information which can be integrated with clinical and pathological data at diagnosis.